2022
DOI: 10.1111/jce.15609
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cardiac mechanical dyssynchrony in left bundle branch area pacing and right ventricular septal pacing using myocardial perfusion scintigraphy in the acute phase of pacemaker implantation

Abstract: Introduction: Left bundle branch area pacing (LBBAP) has recently been reported to be a new, clinically feasible and safe physiological pacing strategy. The present study aims to investigate the usefulness of LBBAP in reducing mechanical dyssynchrony compared with right ventricular septal pacing (RVSP). Methods and Results: A total of 39 LBBAP patients, 42 RVSP patients, and 93 healthy control participants were retrospectively evaluated. We compared phase analysis-(bandwidth, phase standard deviation [PSD], en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Therefore, we used scintigraphy as the evaluation modality for LV synchrony in LBBAP. We previously reported that LBBAP using LLLs reduced mechanical dyssynchrony compared to RVSP and comparable to healthy control participants using myocardial perfusion scintigraphy ( 18 ). This indicates that LBBAP using SDLs may also reduce LV mechanical dyssynchrony compared with RVSP.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Therefore, we used scintigraphy as the evaluation modality for LV synchrony in LBBAP. We previously reported that LBBAP using LLLs reduced mechanical dyssynchrony compared to RVSP and comparable to healthy control participants using myocardial perfusion scintigraphy ( 18 ). This indicates that LBBAP using SDLs may also reduce LV mechanical dyssynchrony compared with RVSP.…”
Section: Discussionmentioning
confidence: 76%
“…LBBAP is a new conduction system pacing method to avoid non-physiological harmful RV pacing. Some reports revealed that LBBAP reduces electrical and dyssynchrony compared to RVP ( 18 , 19 ). Furthermore, the effectiveness of LBBAP in narrowing paced QRS duration and improving LVEF is comparable to that of HBP and biventricular pacing ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different cardiac pacing strategies are currently being used in patients with an indication for permanent pacemaker. Since electrical dyssynchrony has been shown to be associated with heart failure and increased mortality [11], it is important to determine which modality of pacing leads to an electrical behavior closest to the physiological one in patients with normal conduction (narrow QRS).…”
Section: Discussionmentioning
confidence: 99%